Survival assessment of fractured porcelain-fused-to-metal crowns surface roughened by sandblasted and repaired by composite resin after in vitro thermal fatigue - Po-Jen Cheng; Shih-Ming Liu; Ssu-Meng Huang; Jen-Chyan Wang; Chun-Cheng Hung; Wen-Cheng Chen (Journal of Dental Sciences, 2023)
Background/purpose: Intraoral repair usually takes the convenience of the patient's daily life as the starting point, taking into account the bonding strength, operational feasibility, and safety. This study aimed to evaluate the survival of composite resin by simulating cavity fracture repair in porcelain-fused-to-metal (PFM) crowns and referring to the G.V. Black classification of caries as ceramic- and metal-site exposure. Materials and methods: Mechanical sandblast experimental and a nonsandblast control groups comprised 120 samples, and interfacial locking was enhanced through acid etching, bonding, and light-curing composite resin restoration. Classes of VI buccal (B), III mesial (M), and IV mesiobuccal (MB) types, were investigated. Load tests were performed on two sets, with one set at room temperature for 24 h and the other via thermal cycling at 5 °C/50 °C 720 times. Loading was gradually applied to the samples until a maximum of 450 N was reached. Results: Results showed that 24 h survival rates of B-, M − , and MB-repaired PFM crowns were 88%, 84%, and 88%, respectively. The repaired PFM survival rates for B, M, and MB were 52%, 44%, and 28%, respectively, after thermal cycling and loading tests. Multiple logistic regression and chi-square test (α = 0.05) showed that the regression results of factors affecting survival assessment were only significant between groups after thermal fatigue (P < 0.05). Survival rate of repairing metal-site in the MB model was significantly higher than that of ceramic-sites repairing in non-blasted samples. For the MB cavity model, sandblasting can significantly improve the survival rate of the repair of ceramic parts in the MB model (P < 0.05). Conclusion: Our results suggest that sandblasting can be further considered, especially for MB cavity fractures when ceramic-site restorations are required.